Differentiation of Homonyms in Related Slavic Languages - Ткаченко, Анастасія (Київського національного університету імені Тараса Шевченка, 2024)
The classification of homonyms occupies an important place in the study of the phenomenon of homonymy in any language. This is evidenced by the large number of works devoted to homonymy, in which the authors propose one or another approach to the selection of types of homonyms. The lexical-semantic structuring of homonyms is based, on the one hand, on the traditional division of them into full, when the meaning of a polysemous or unambiguous word does not match, or partial, when the differences are expressed taking into account the common elements of the semantic structure of lexical units, however, such a division does not exhaust the entire complex systematically -structural characteristics of the studied units. The topic of Ukrainian-Czech-Polish cross-linguistic homonymy is relevant from both a theoretical and a practical point of view. From a theoretical point of view, the very definition of the concept of interlingual homonymy, that is, the “identical” sounding of words belonging to different languages, the establishment of correspondences that would make it possible to recognize two similar- sounding lexical units as interlingual homonyms seem quite interesting. From a practical point of view, it should be noted that the “insidious translator’s friends” cause many mistakes during communication or translation. Some errors arise from differences in meaning, others are purely stylistic. Today, there is a need to study the lexical-semantic and functional-stylistic differences between closely related languages, namely between Ukrainian, Czech, and Polish languages, which are completely or partially identical in terms of expression. It is important to determine the degree of semantic distance or relatedness in cross-language homonyms of the above-mentioned languages in order to prevent unwanted translation errors in the future. Therefore, the relevance of the study is determined by the need for a clearer classification and a more complete analysis of the peculiarities of the functioning of cross-language homonyms (based on the material of the Ukrainian, Czech, and Polish languages). Despite the large number of studies on cross-language homonymy, the causes and results of the emergence of new meanings have not yet been thoroughly studied in modern linguistics words The chosen topic belongs to a wide range of the most important modern linguistic issues related to the problems of linguistic and cultural communication, language development and its current state, lexical semantics, etc. Scientific research is devoted to the complex structural and semantic characteristics of Czech-Polish-Ukrainian cross-linguistic homonymy.

Класифікація омонімів займає важливе місце у дослідженні явища омонімії будь-якої мови. Про це свідчить велика кількість робіт, присвячених омонімії, в яких автори пропонують той чи інший підхід до виділення типів омонімів. Лексико-семантичне структурування омонімів спирається, з одного боку, на традиційний поділ їх на повні, коли значення багатозначного чи однозначного слова не співпадає, чи часткові, коли відмінності виражаються, враховуючи спільні елементи семантичної структури лексичних одиниць, але такий поділ не вичерпує усього комплексу системно-структурних характеристик досліджуваних одиниць. Тема українсько-чесько-польської міжмовної омонімії актуальна як з теоретичного, так і з практичного погляду. З теоретичної точки зору досить цікавим здається саме визначення поняття міжмовної омонімії, тобто “ідентичного” звучання слів, що належать різним мовам, встановлення відповідностей, що давали б змогу визнати дві подібні за звучанням лексичні одиниці за міжмовні омоніми. Щодо практичного погляду, слід зауважити, що “підступні друзі перекладача” спричиняють безліч помилок під час спілкування чи перекладу. Деякі помилки виникають з різниць у значенні, інші лише стилістичні. На сьогоднішні існує необхідність дослідження лексико-семантичних та функціонально-стилістичних розбіжностей між близькоспорідненими мовами, а саме між українською, чеською, польською мовами, які за планом вираження є повністю або частково тотожними. Визначити ступінь семантичної віддаленості або спорідненості у міжмовних омонімах вищевказаних мов є важливим для запобігання в подальшому небажаних помилок при перекладі. Отже, актуальність дослідження визначається потребою більш чіткої класифікації та більш повним аналізомособливостей функціонування міжмовних омонімів (на матеріалі української, чеської, польської мов). Незважаючи на велику кількість досліджень міжмовної омонімії, у сучасному мовознавстві ще досконально не вивчені причини та результати виникнення нових значень слів. Обрана тема належить до широкого кола найважливіших сучасних мовознавчих питань, що стосуються проблем лінгво-культурної комунікації, розвитку мови та її сучасного стану, лексичної семантики тощо. Наукову розвідку присвячено комплексній структурно-семантичній характеристиці чесько-польсько-української міжмовної омонімії.
Диференціація омонімів у споріднених слов’янських мовах
Keywords: cross-linguistic homonymy; phonetic-graphic; phonetic; graphic and morphological homonyms; міжмовна омонімія; фонетико-графічні омоніми; фонетичні омоніми; графічні омоніми; морфологічні омоніми